PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI OPERASI HIMPUNAN DI KELAS VII SMP NEGERI 19 PALU - Asnidar, Asnidar (Jurnal Elektronik Pendidikan Matematika Tadulako, 2014)
This research aim to obtain a description the implementation of the application cooperative learning model NHT type in effort to improve learning outcomes VII grade students of SMP Negeri 19 Palu on the set operations matter. Kind of this research is classroom action research which refers to the design of Kemmis and Mc Taggartâs model. The data obtained in this study are presented qualitatively and quantitatively analyzed. Based on the result of research conducted in class VII SMP Negeri 19 Palu there is a significant improvement from pre-test to the first cycle of action and to the second cycle.